Applying SVM for Foot Pressure Pattern Classification - Pan Wentao; Peng Zhaoqin; Caochun Li Bo (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
An automatic loading simulation and testing system of steering servo was designed in this paper. Design of hardware and software of the testing system were illustrated, and the Load testing principle and test strategy were analyzed. Torque servo motor was used to simulate the loading added to the steering servo. The torque magnitude was controlled proportional to the angular displacement of the steering servo to simulate elastic load. Fuzzy PID control algorithm was used to make torque servo motor follow the change of angular displacement quickly and accurately. The effectiveness of the automatic testing system was proved by the experimental results. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4277